Cloning and expression analysis of a transcription factor gene BoWRKY3 from Brassica oleracea var. italica - CHEN Bei-bei; JIANG Ming; MIAO Li-xiang; LI Wen-ping (浙江大学学报. 农业与生命科学版, 2012)
A WRKY transcription factor gene, designated BoWRKY3 (accession number: JN120758), was amplified from leaves of Brassica oleracea var. italica, and the sequence analysis was performed. The expression patterns of BoWRKY3 in leaves before and after downy mildew challenge were analyzed by reverse transcription-polymerase chain reaction (RT-PCR). Sequencing results indicated that the genomic DNA was 1 136 bp in length with 3 introns of 81, 101 and 96 bp, respectively. The complete coding sequence was 858 bp encoding 285 amino acids, including a conserved WRKYGQK domain and a CX5CX23HX1H zinc finger structure. RT-PCR analysis showed that the highest expression levels of BoWRKY3 were observed at 6-36 h induced by Hyaloperonospora parasitica, suggesting that its function was possibly related with downy mildew resistance. Sequence alignment results showed that there were very little differences between BoWRKY3 and homologous genes of Cruciferae plants, however, major differences were observed between BoWRKY3 and those of Gramineae plants, revealing their large genetic distance.